ERROR ANALYSIS ON SENTENCE CONSTRUCTION BY USING GRAMMAR TRANSLATION METHOD TO THE FIRST SEMESTER STUDENTS OF ARABIC EDUCATION STUDY PROGRAM AT DATOKARAMA STATE ISLAMIC UNIVERSITY PALU - Afifah Afifah (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This is a qualitative research focusing on answering the research question, “What kinds of error occur on sentence construction by using Grammar Translation Method to the first semester students of Arabic Education Study Program at Datokarama State Islamic University Palu?” The participants of this research are thirty two first semester students of Arabic Education Study Program at Datokarama State Islamic University Palu. The instrument of the research is a document analysis of a hundred Indonesian sentences translated into English. The result of this research shows that there are five types of error occurred: (1) omission; (2) addition; (3) misformation; (4) misorder; and (5) word misuse. Omission errors can be found on the article for the singular nouns, -s/-es ending for plural marker of nouns, to be in nominal sentences, measured quantities for uncountable nouns, and –s/-es ending for verbs in simple present tense. When the mother tongue interferes the sentence construction, the addition errors then took place. Misformation errors occurred on the use of demonstrative determiners, subject-verb agreement in present perfect tense as well as in nominal sentences. Misorder errors can be showed on the word order of present perfect tense. Word misuse errors occurred when the participants translated the sentences one word by one word literally while the vocabulary is not sufficient